Nonequilibrium Plasma‐Activated Antimicrobial Solutions are Broad‐Spectrum and Retain their Efficacies for Extended Period of Time1. Issue 6 (12th April 2013) - Ercan, Utku K.; Wang, Hong; Ji, Haifeng; Fridman, Gregory; Brooks, Ari D.; Joshi, Suresh G.
Abstract By applying dielectric‐barrier discharge nonthermal plasma technique, we have treated fluids and generated antimicrobial solutions, tested for properties such as changes in pH, temperature, delay time, holding time, fluid‐aging, and detection and comparison of acid and hydrogen peroxide. All plasma‐treated solutions showed strong biocidal activity, and among them, NAC solution was the most powerful, inactivated biofilms of tested microorganisms in 15 min of holding time. During accelerated aging experiments, plasma‐treated NAC solution exhibited the equivalent of two years of shelf. These results indicate that it retained its antimicrobial properties for an extended period against a wide range of multidrug‐resistant pathogens, making it an excellent candidate for further testing in vivo.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>